2014
DOI: 10.1521/soco.2014.32.4.315
|View full text |Cite
|
Sign up to set email alerts
|

The First Cut is the Deepest: Effects of Social Projection and Dialectical Bootstrapping on Judgmental Accuracy

Abstract: As a judgmental heuristic, social projection improves the accuracy of social consensus estimates. Aggregating multiple estimates, even within individuals, also increases accuracy. In the current research we combine these two lines of study and find that, within individuals, second estimates are less projective and less accurate than first estimates. Bootstrapped, or averaged, estimates yield no improvements in correlational measures of accuracy, but do show accuracy gains in deviation-based accuracy scores. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…A long line of research demonstrates that people engage in "social projection" of this kind when asked to make information-deprived judgments of other people (reviewed in Krueger, 2007;Robbins & Krueger, 2005). The logic behind the utility of social projection is that-because most people are in the majority most of the time-projection allows people to make quick and reasonably accurate judgments (on average) about unknown others (Krueger, 2007;Krueger & Chen, 2014). Indeed, in our studies subjects received only sparse information about the other players (i.e., only their party affiliation); providing good conditions for social projection.…”
Section: Discussionmentioning
confidence: 99%
“…A long line of research demonstrates that people engage in "social projection" of this kind when asked to make information-deprived judgments of other people (reviewed in Krueger, 2007;Robbins & Krueger, 2005). The logic behind the utility of social projection is that-because most people are in the majority most of the time-projection allows people to make quick and reasonably accurate judgments (on average) about unknown others (Krueger, 2007;Krueger & Chen, 2014). Indeed, in our studies subjects received only sparse information about the other players (i.e., only their party affiliation); providing good conditions for social projection.…”
Section: Discussionmentioning
confidence: 99%
“…S-T, and S-O-T) overestimate the prevalence of selfenhancement error. The overdiagnosis of self-enhancement is of theoretical and practical interest because it implies a reverseinference fallacy (Krueger, 2014;Wason, 1960). In propositional logic, a reverse inference is invalid.…”
Section: The Decision-theoretic Indexmentioning
confidence: 99%
“…The benefits of averaging multiple estimates provided by the same person have been demonstrated for various general knowledge quantities (proportions [3,5,6,8,11], historical dates [4,8], and correlations [12]). However, evidence of averaging benefits is somewhat mixed for both general knowledge questions without clear-cut boundaries for reasonable answers [8,9] and estimates of social consensus (a correlational accuracy measure showed no benefits, but a deviation-based accuracy measure did) [7], and the only study investigating the quality of confidence judgments found no benefits of harnessing the inner crowd [13]. In summary, most -but not all -studies have found evidence for the wisdom of the inner crowd.…”
Section: How Wise Is the Inner Crowd?mentioning
confidence: 99%
“…Since Galton's demonstration of the 'wisdom of crowds' [2], research in psychology, economics, political science, biology, statistics, and computer science has time and again demonstrated how aggregating diverse judgments frequently -and sometimes dramatically -increases accuracy because nonredundant errors cancel each other out. Surprisingly, a lone individual can also enlist the wisdom of crowds by averaging selfgenerated, nonredundant estimates [3][4][5][6][7][8][9][10][11][12]. We review evidence for this 'wisdom of the inner crowd', and consider how it can be produced, how its accuracy can be improved, and whether people use it to their advantage.…”
mentioning
confidence: 99%